Production model based on lean manufacturing tools to reduce delivery times in a small manufacturing enterprise - Francia Barba, Mariafe Olenka (2025)
The foam furniture paint industry, belonging to the manufacturing sector, has experienced a decline in recent years due to the COVID-19 pandemic. This situation has negatively impacted production capacity and has generated significant challenges. Among them, reprocessing has occurred due to undesired tones in the paints, the presence of residues in the machines, as well as errors in machinery programming and delays in the start of production. These factors have hindered the manufacturing sector from reaching its pre-crisis economic level. Consequently, delays in the delivery of the final product arise, leading to economic losses for the companies, which hinder their development. To address these issues and thereby reduce product delivery times, the production improvement model based on Lean Manufacturing tools is proposed. The model consists of tools such as 5S, Poka-Yoke, and standardized work. The model was validated through the implementation of pilot tests and simulation using Arena software.